2016
DOI: 10.1038/srep26358
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of ho-1 protects the striatum from ferrous iron-induced injury in a male-specific manner in mice

Abstract: Men have worse survival than premenopausal women after intracerebral hemorrhage (ICH). After ICH, overproduction of iron associated with induction of heme oxygenase-1 (HO-1) in brain was observed. Rodent ICH model using ferrous citrate (FC)-infusion into the striatum to simulate iron overload, showed a higher degree of injury severity in males than in females. However, the participation of HO-1 in sex-differences of iron-induced brain injury remains unknown. The present results showed a higher level of HO-1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…1F). HO-1 is strongly linked to oxidative stress, and previous reports have demonstrated that HO-1 is a key factor in aggravating the ICH condition 37,38 .…”
Section: Discussionmentioning
confidence: 91%
“…1F). HO-1 is strongly linked to oxidative stress, and previous reports have demonstrated that HO-1 is a key factor in aggravating the ICH condition 37,38 .…”
Section: Discussionmentioning
confidence: 91%
“…After 72 hours, the above changes weakened, but still higher than the normal group. Study by Wang et al19 showed that overexpression of HO-1 has damaging effects on ICH brain injury induced by ferrous citrate.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of HFE and H-ferritin was observed in 6-month old H67D mice, alongside astrogliosis, increased protein oxidation, expression of and HO-1, suggestive of heightened metabolic and oxidative stress. Accordingly, the striatum of HO-1 knockout mice was protected from iron-mediated injury in males but not females (Wang et al, 2016b ). Meanwhile, H67D mice at 12-months had augmented H- and L-ferritin accompanied by attenuated Tf expression, indicating increased storage of iron (Nandar et al, 2013 ).…”
Section: Effect Of Systemic Iron Overload On Brain Ironmentioning
confidence: 99%